How can ethical leadership increase employees' bootlegging innovation behavior in China?: a serial mediation model of psychological wellbeing and psychological entitlement - Zhang, Junzhu; Choi, MyeongCheol; Wang, Kaiyuan; Kim, Hann Earl (Frontiers in Psychology, 2025)
Bootlegging innovation behavior poses challenges to organizational management but significantly contributes to development and innovation. The relationship between leadership style and bootlegging innovation behavior is particularly noteworthy. Ethical leadership often instills a sense of reliability and integrity in employees, fostering trust and reciprocity, which benefits both leaders and the organization. To investigate how ethical leadership enhances employees' willingness to innovate and engage in innovative behavior, this study collected survey data from 382 private-sector employees in southeast China. The findings revealed a positive correlation between ethical leadership and bootlegging innovation behavior. Furthermore, psychological wellbeing and psychological entitlement were found to mediate the relationship between ethical leadership and bootlegging innovation behavior. The integrity and inclusiveness demonstrated by ethical leadership help employees feel valued, enhancing their psychological wellbeing. This, in turn, increases their psychological entitlement and willingness to realize their self-worth, making them more inclined to put innovative ideas into practice—even without explicit authorization. The key contribution of this study lies in identifying the chain-mediating effect of psychological wellbeing and psychological entitlement in the relationship between ethical leadership and bootlegging innovation behavior. By exploring this complex and nuanced process, the study provides actionable recommendations for fostering bootlegging innovation behavior among employees. It also broadens the research scope of bootlegging innovation and offers fresh perspectives for future research endeavors.